2007
DOI: 10.1194/jlr.m700108-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate increases HDL-cholesterol by reducing cholesteryl ester transfer protein expression

Abstract: In addition to efficiently decreasing VLDLtriglycerides (TGs), fenofibrate increases HDL-cholesterol levels in humans. We investigated whether the fenofibrateinduced increase in HDL-cholesterol is dependent on the expression of the cholesteryl ester transfer protein (CETP). To this end, APOE*3-Leiden (E3L) transgenic mice without and with the human CETP transgene, under the control of its natural regulatory flanking regions, were fed a Westerntype diet with or without fenofibrate. Fenofibrate (0.04% in the die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 72 publications
5
73
0
1
Order By: Relevance
“…However, APOE*3Leiden mice (like WT mice) do not possess a CETP gene, and therefore these mice do not respond to HDL-modulating interventions. By crossbreeding the APOE*3Leiden mice to mice expressing the human CETP gene ( 75 ), APOE*3Leiden.CETP mice were obtained that respond to both lipid-lowering as well as HDL-raising interventions (50)(51)(52)(53)76 ). In the current study, we found signifi cant lowering effects of anti-PCSK9 antibodies on TC and TG levels in APOE*3Leiden.CETP mice, but HDL-C was not affected (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, APOE*3Leiden mice (like WT mice) do not possess a CETP gene, and therefore these mice do not respond to HDL-modulating interventions. By crossbreeding the APOE*3Leiden mice to mice expressing the human CETP gene ( 75 ), APOE*3Leiden.CETP mice were obtained that respond to both lipid-lowering as well as HDL-raising interventions (50)(51)(52)(53)76 ). In the current study, we found signifi cant lowering effects of anti-PCSK9 antibodies on TC and TG levels in APOE*3Leiden.CETP mice, but HDL-C was not affected (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The APOE*3Leiden.CETP mice are a well-established mouse model for familial dysbetalipoproteinemia with human-like lipoprotein metabolism and atherosclerosis development, which respond in a human-like manner to both lipid lowering as well as HDLraising drugs (like statins, fi brates, niacin, etc.) used in the treatment of CVD (49)(50)(51)(52).…”
Section: In Vivomentioning
confidence: 99%
“…Mice, Diet, and Salsalate Treatment E3L.CETP mice were obtained as previously described (7)(8)(9). To assess the effect of salsalate on progression of obesity, dyslipidemia, and hyperglycemia, 10-week-old male E3L.CETP mice were randomized to receive an HFD (45% kcal lard fat; Research Diets) without or with 0.5% (weight for weight [w/w]) salsalate (2-carboxyphenyl salicylate; TCI Europe N.V.) for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of the current study was to investigate the mechanisms underlying the beneficial effects of salsalate on lipid and glucose metabolism by treating APOE*3-Leiden.CETP (E3L.CETP) transgenic mice, a wellestablished model for human-like lipoprotein metabolism (7)(8)(9), with salsalate mixed through the high-fat diet (HFD). We found that salsalate both prevented and reduced HFD-induced weight gain by lowering fat mass accumulation, and improved glucose and lipid metabolism.…”
mentioning
confidence: 99%
“…HDL-C raises results from the increased expression of apoA-II and, at a much lesser extent, apoA-I (Yetukuri et al 2011), as well as to the enhanced cholesterol efflux via the induction of ABCA1 in the liver (Berger et al 2005). In addition, animal studies have shown that fenofibrate reduces CETP hepatic expression (van der Hoogt et al 2007). …”
Section: Fibratesmentioning
confidence: 99%